Effectiveness of water fluoridation in caries reduction in a remote Indigenous community in Far North Queensland. (14th July 2014) - Johnson, NW; Lalloo, R; Kroon, J; Fernando, S; Tut, O
Abstract Background Children in remote Indigenous communities in Australia have levels of dental caries much greater than the national average. One such, the Northern Peninsula Area of Far North Queensland (NPA), had an oral health survey conducted in 2004, shortly before the introduction of fluoridated, reticular water. Children were again surveyed in 2012, following five years exposure. Methods An oral examination was conducted on all consenting children enrolled in schools across the community, using WHO Basic Oral Health Survey methodology. Results Few teeth had restorations in both surveys. Age‐weighted overall caries prevalence and severity declined from 2005 to 2012 by 37.3%. The effect was most marked in younger children, dmft decreasing by approximately 50% for ages 4–9 years; at age 6, mean decayed score decreased from 5.20 to 3.43. DMFT levels also decreased by almost half in 6–9 year olds. However, significant unmet treatment needs exist at all ages. Conclusions There has been considerable improvement in child dental health in the NPA over the past 6–7 years. In light of continued poor diet and oral hygiene, water fluoridation is the most likely explanation. The cost‐effectiveness for this small community remains an issue which, in the current climate of political antagonism to water fluoridation in many quarters, requires continued study.